Aspects of development of continental combined transport in the Czech Republic - Široký, Jaromír; Hlavsová, Pavlína; Chalupová Vohánková, Hana (City Net Scientific Research Center, 2016)
This paper describes the current state of combined transport, and especially continental transport, in the Czech Republic, and aspects of its potential further development. The role of continental CT is particularly important in logistics chains, mainly in transporting palletised goods.
Aspekty rozvoje kontinentální kombinované dopravy v ČR
Keywords: combined transport; continental transport; logistics chains; development; kombinovaná doprava; kontinentální doprava; logistický řetězec; vývoj